Enhancing EFL Learner Engagement in Large Classrooms through Padlet - Komilie Situmorang; Santa Maya Pramusita; Bima Adi Saputra (AL-ISHLAH: Jurnal Pendidikan, 2025)
Engaging students in English as a Foreign Language (EFL) classrooms, particularly large ones, remains a persistent challenge due to rigid structures and limited opportunities for interaction. While gamification is commonly used to boost engagement, its competitive elements can trigger anxiety and hinder participation, especially among less confident learners. This study employed an explanatory sequential mixed methods design to explore the effectiveness of Padlet—a non-competitive, collaborative digital platform—in promoting student engagement. A total of 202 first-year nursing students participated in a 14-week course in which Padlet was integrated into classroom activities. Data were collected through a Likert-scale questionnaire and semi-structured interviews with selected participants. Quantitative findings indicated high levels of agreement across five engagement dimensions: motivation, interactivity, learning opportunities, ease of use, and language learning support. Qualitative analysis revealed four dominant themes: Padlet's social media-like appeal, its role in facilitating safe and active collaboration, the creation of an interactive classroom atmosphere, and peer learning through shared content. Students reported increased willingness to participate, reduced anxiety, and greater comfort in expressing ideas. Padlet functioned as a low-anxiety, learner-centered space that encouraged participation, particularly among shy or low-proficiency students. While it may not directly improve language proficiency, its affective benefits foster a positive foundation for language development. Padlet offers an inclusive, psychologically safe alternative to competitive gamification, making it a valuable tool for enhancing student engagement in large EFL classrooms.